ASSOCIATION OF ABDOMINAL OBESITY WITH CAROTID ARTERY DISEASE - Deleva Stoshevska, Tatjana (Journal of Morphological Sciences, 2020)
Introduction : Abdominal obesity (AO) is a condition of excessive abdominal fat deposited to such an extent that it is likely to have a negative impact on health. Carotid artery disease (CAD) usually involves atherosclerotic changes in the arterial wall. CAD is a significant risk factor for cerebrovascular insult (CVI) and transient ischemic attack (TIA). Objective : To show whether there is an association of AO with CAD in our study group. To determine the prevalence of CAD in the subjects with or without AO. To determine the prevalence of asymptomatic and symptomatic CAD in all these subjects. Materials and methods : This cross-sectional study included 73 subjects divided into a study (42 subjects with AO) and a control group (31 subjects without AO), aged 41 to 74 years. AO was determined by measuring waist circumference according to NCEP ATP III criteria reference points; Extracranial carotid evaluation was performed ultrasonographically with a linear probe with a frequency of 7.5 MHz. CAD assessment was performed using Ultrasound Consensus Criteria for Carotid Stenosis. Results : The study group showed a higher incidence of CAD than the control group, but statistically not  significant (p>0.05). In the study group 25 subjects (59.52%) had CAD, 7 subjects (28%) were symptomatic, while 18 subjects (72%) were asymptomatic. In the control group 16 subjects had CAD (51.61%), 3 subjects were symptomatic (18.75%), while 13 subjects (81.25%) were asymptomatic. Conclusion : Although this study did not show a significant association between AO and CAD, early carotid ultrasound examination is necessary to diagnose CAD in AO subjects, which would achieve effective prevention of CVI and TIA. More powerful studies with much larger number of subjects are needed. Keywords : abdominal obesity, carotid artery disease, cerebrovascular stroke, transient ischemic attack.